Between religion and politics: the political deification of Mahishasur - Sen, Moumita (Religion, 2022)
This article focuses on the political deification of a so-called demon Mahishasur in hegemonic Hindu myths. The Mahishasur movement is a social movement for caste equality headed by indigenous and oppressed-caste groups against the hegemonic upper caste Hindu storyworlds which dominate Indian politics, society, and culture. In this article, I use data collected through participant observation and long interviews to focus on the way political organisers select and create icons for this movement, how the participants in the movement behave around these icons, and finally what terms do they use to understand their own practices. I use three related aspects of the movement – icons, rituals, and discourse – to bring out the emic concepts and practices around political deification used in the Mahishasur movement.